Pengalaman dosen dalam penggunaan simulasi sebagai metode pembelajaran di Akademi Keperawatan Ibnu Sina - Aida Khairunisa; Rosa Galica Gita Gressia; Noor Aznidar Aldani; Pulung Herdianto (Poltekkes Kemenkes Aceh, 2024)
Background: The application of simulation method is one of the keys to improve students' practical skills. However, many lecturers face challenges in integrating simulation effectively, mainly due to limited facilities, lack of training, and difficulty in measuring learning impact.Objectives: This study aims to explore how lecturers' experiences in implementing simulation methods, especially related to the strengths, challenges, student responses and the role of institutions related to simulation methods.Methods: This design is a qualitative study with a descriptive phenomenological approach involving seven nursing educators with in-depth interviews at the Akademi Keperawatan Ibnu Sina Kota Sabang. Data analysis used the Miles and Huberman Model which refers to data collection, data reduction, data presentation, and drawing conclusions.Results: There are four main themes in this study, namely the strengths of the simulation method, challenges of the simulation method, student responses and the role of educational institutions.Conclusion: The simulation method makes students more interactive, makes it easier to elaborate on the topics being studied, make decisions, gain direct experience, think critically and work together in a team.